Trade Reform in Vietnam : Opportunities with Emerging Challenges - Auffret, Phillipe (World Bank, Washington, DC, 2014)
In 1986 Vietnam initiated a transition from a centrally planned economy to a market-oriented economy where the government would keep playing a leading role. These renovation (doi moi) policies were successful at generating economic growth and reducing poverty. In the ten-year socioeconomic strategy endorsed by the Ninth Party Congress in April 2001, the authorities further articulated their development objectives in terms of economic growth and poverty reduction. To reach these objectives, the government indicated that its structural reform priorities were to change Vietnam's trade and financial policies, liberalize the climate for private investment, increase the efficiency of public enterprises, and improve governance. The author argues that the pace of implementation of trade reform-which has been impressive so far-is raising new challenges. On one side, fast liberalization of trade reform may soon conflict with the slow pace of implementation of other reforms, including restructuring of state-owned enterprises and state-owned commercial banks. On the other side, Vietnam would greatly benefit from fast implementation of trade reform and particularly fast accession to the World Trade Organization (WTO), especially after China's recent WTO accession. Auffret concludes that implementation of trade reform will be a testing ground to reveal the extent of Vietnam's commitment to a market-oriented economy.